The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1042/bsr20190414
|View full text |Cite
|
Sign up to set email alerts
|

A gene signature predicts response to neoadjuvant chemotherapy in triple-negative breast cancer patients

Abstract: Triple-negative breast cancer (TNBC) accounts for approximately 15% of all breast cancer cases. TNBC is highly aggressive and associated with poor prognosis. The present study aimed to compare gene expression between TNBC patients with pathological complete response (pCR) and those with not complete response (nCR) to neoadjuvant chemotherapy. Microarray data of 16 TNBC patients received neoadjuvant chemotherapy were identified from the Gene Expression Omnibus database and 10 patients of them had pCR. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[ 8 9 10 ] Increasing studies have found that lncRNAs exist abnormal expression and related to prognosis in BC. [ 11 12 13 ] However, there are few studies on the prognostic value of uniting biomarkers and other clinical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 9 10 ] Increasing studies have found that lncRNAs exist abnormal expression and related to prognosis in BC. [ 11 12 13 ] However, there are few studies on the prognostic value of uniting biomarkers and other clinical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lncRNAs not only participate in the process of chemoresistance, but can also be used for predicting the response to neoadjuvant chemotherapy in TNBC. Zheng et al 110 systematically compared gene expression between TNBC patients with pathological complete response and those without a complete response to neoadjuvant chemotherapy and ultimately developed a gene signature of 2 coding genes and 3 lncRNAs to predict the response to neoadjuvant chemotherapy of TNBC patients.…”
Section: Long Non‐coding Rnasmentioning
confidence: 99%
“…13 Recently, plenty of gene signatures have become biomarkers for guiding treatment in various cancers. [14][15][16] Multigene prognostic sets can predict the tumor prognosis more accurately than a single gene, which enable more effective treatment of cancer patients. 17,18 Identifying the hallmark gene signature is important for clinical application and precision medicine of cancers.…”
Section: Introductionmentioning
confidence: 99%